Prognostic Value of Plasma Epstein-Barr Virus DNA Levels Pre- and Post-Neoadjuvant Chemotherapy in Patients With Nasopharyngeal Carcinoma - Zhu, Lisheng; Ouyang, Tao; Xiong, Ying; Ba, Li; Li, Qiuting; Qiu, Mengjun; Zou, Zhenwei; Peng, Gang (Frontiers in Oncology, 2021)
Background: In this study, we evaluated the prognostic value of the plasma levels of Epstein-Barr virus (EBV) DNA in patients with nasopharyngeal carcinoma (NPC) at different treatment stages. Methods: We retrospectively analyzed the data of 206 patients with NPC. Pre-neoadjuvant chemotherapy (pre-NACT), post-NACT, post-radiotherapy, and post-treatment plasma EBV DNA levels were used to establish prognostic nomograms. The concordance index (C-index) and calibration curves were used to compare the prognostic accuracy of the nomograms. The results were confirmed in a validation cohort consisting of patients who were tested for EBV DNA levels at all four stages of treatment. The Kaplan-Meier method was used to calculated progression-free survival (PFS) and overall survival (OS). Survival differences were analyzed using the log-rank test. Results: EBV DNA-positive patients had worse 3-year PFS and 5-year OS than EBV DNA-negative patients; this was true for pre-NACT (PFS: 82.7% vs. 57.3%, P < .001; OS: 90.9% vs. 68.7%. P =.08) and post-NACT (PFS: 85.0% vs. 50.6%, P < .001; OS: 91.7% vs. 65.7%; P = .001) EBV DNA levels but not for post-radiotherapy (PFS: 72.2% vs. 60.9%, P = .192; OS: 73.1% vs. 77.2%, P = .472) or post-treatment (PFS: 77.3% vs. 59.2%, P = .063; OS: 77.5% vs. 79.7%, P = .644) levels. Nomograms combining pre-NACT and post-NACT EBV DNA levels had superior prognostic ability than those of post-radiotherapy and post-treatment EBV DNA levels. Conclusion: Pre-NACT EBV DNA levels combined with post-NACT EBV DNA levels can more reliably predict survival outcomes in patients with NPC.